Five Stories (Translated from the Arabic by Nedelya Kitaeva) - Kitaeva, Nedelya (Sledva : NBU Journal of Humanities and Arts, 2020)
Five stories by the Oman writer and Man Booker International prize winner Jokha al-Harthi full of vigor and color, subdued emotions, subtle social and gender insights. SLEDVA is proud to host this first appearance of the author in Bulgarian. The stories are selected and translated from the Arabic by Dr. Nedelya Kitaeva, who is teaching Arabic language and Culture at the New Bulgarian University.